Mistuned Dynamic Response Analysis of Series Mechanism - Yu Linchong; Lin Zhishu; Lin Xingyan (Jixie chuandong)
The series periodic mechanism has mistuned dynamic response and peculiarity. The series mechanism model is set up based on theory and method of multi- body dynamics. The mistuned mechanism modeling method is proposed and mistuned dynamic responses of a normal series periodic mechanism such as solar panel deployable mechanism under the stochastic mistuning is simulated. The results show that mistuned dynamic responses are common in series periodic mechanism. While rigid series periodic mechanism has localization of mistuned dynamic responses.